Effects of washing of the face with a mild facial cleanser formulated with sodium laureth carboxylate and alkyl carboxylates on acne in Japanese adult males. Issue 2 (13th August 2014) - Isoda, K.; Takagi, Y.; Endo, K.; Miyaki, M.; Matsuo, K.; Umeda, K.; Umeda‐Togami, K.; Mizutani, H.
<x xml:space="preserve">Abstract</x> Background/purpose Washing the face with a mild cleanser is generally recommended for acne care. Occasionally, the general public has the misconception that acne is exacerbated by cleansers and furthermore it has concerns about inducing skin irritation and xerosis by intensive washing. Recently, we developed a new cleanser based on sodium laureth carboxylate and alkyl carboxylates (AEC/soap) that cleans sebum well without penetrating the stratum corneum. Methods We designed a controlled clinical trial conducted on adult Japanese males with moderate or less acne. Twenty subjects washed their faces with AEC/soap base cleanser twice a day for 4 weeks. Assessment of the efficacy was conducted prior to the start of the study, and at the end of weeks 2 and 4. Results Significant improvement of the acne was observed within 2 weeks, and acne lesions were not detectable in 25% of the subjects at week 4. Sebum secretion levels on the skin significantly increased on the forehead, but significantly decreased on the cheek which correlated with the improvement. No complaints of dryness or irritation occurred during the study. Conclusion Washing the face twice a day with facial cleanser based on AEC/soap is an effective care for moderate or less grade facial acne.